2019
DOI: 10.1016/j.semarthrit.2019.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The adjusted global antiphospholipid syndrome score (aGAPSS) and the risk of recurrent thrombosis: Results from the APS ACTION cohort

Abstract: Objectives:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 18 publications
2
62
0
7
Order By: Relevance
“…Based on additional registry analyses completed over the last decade, APS ACTION investigators demonstrated that (a) the adjusted global APS Score (aGAPSS) might help risk stratifying patients based on the likelihood of developing recurrent thrombosis in APS [ 13 ]; (b) younger age at diagnosis of obstetric APS, additional CVD risk factors, history of superficial vein thrombosis and heart valve disease, multiple aPL test positivity, and higher aGAPSS at the registry entry increase the risk of thrombosis after initial pregnancy morbidity [ 14 ]; and (c) combined antiplatelet and anticoagulant therapy, compared to single therapy, may decrease the rate of and increase the time to thrombosis recurrence in patients with APS presenting with arterial thrombosis [ 15 ].…”
Section: –2020: the Evolution Of Aps Actionmentioning
confidence: 99%
“…Based on additional registry analyses completed over the last decade, APS ACTION investigators demonstrated that (a) the adjusted global APS Score (aGAPSS) might help risk stratifying patients based on the likelihood of developing recurrent thrombosis in APS [ 13 ]; (b) younger age at diagnosis of obstetric APS, additional CVD risk factors, history of superficial vein thrombosis and heart valve disease, multiple aPL test positivity, and higher aGAPSS at the registry entry increase the risk of thrombosis after initial pregnancy morbidity [ 14 ]; and (c) combined antiplatelet and anticoagulant therapy, compared to single therapy, may decrease the rate of and increase the time to thrombosis recurrence in patients with APS presenting with arterial thrombosis [ 15 ].…”
Section: –2020: the Evolution Of Aps Actionmentioning
confidence: 99%
“…14 In fact, CVD risk factors are now incorporated into thrombosis prediction models. 15 , 16 Lastly, overlapping manifestations exist between SLE and APS. While aPL modify the clinical presentation of SLE patients, 17–19 conversely, SLE could also modify the clinical presentation of aPL-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…79 The adjusted GAPSS has been applied to asses the risk of recurrent thrombosis in the APS ACTION cohort and for risk stratification in young APS patients with acute myocardial infarction. 80,81 Statins: Obstetric APS. The global prevalence of preeclampsia, a leading cause of maternal and fetal mortality, is estimated to be 4.6% (95% CI 2.7%-8.2%) of primigravidae.…”
Section: Statinsmentioning
confidence: 99%
“…79 The adjusted GAPSS has been applied to asses the risk of recurrent thrombosis in the APS ACTION cohort and for risk stratification in young APS patients with acute myocardial infarction. 80,81…”
Section: Adjunctive Therapiesmentioning
confidence: 99%